FUNCTIONAL INDEPENDENCE OF AMPUTEES TRANSTIBIAL PROSTHESES (Fiep Bulletin - online, 2014)
Introduction: Amputation is a word derived from the Latin meaning partial or total withdrawal of a member or more, may be surgical or traumatic, and amputations have various causes such as trauma, vascular processes, thrombosis, tumor, infectious among others. The level of amputation can also vary and the main transtibial and transfemoral are all characteristics that refer to amputation as the amputation height whether short or long average are interesting at the time of assessment whether physical or functional. Objective:Check level of functional independence in patients clinic of the Faculty of Assisi Gurgacz with transtibial amputations towards their functional capabilities, using the Media Functional Amputee (FMA). Methodology: This research is in a field study, cross-sectional, quantitative trait, data collection of primary source, and the research sample consisted of 19 individuals, as follows: 5 female and 14 male. Data were collected at the rehabilitation center of Assisi School Gurgacz - FAG in the city of Cascavel - PR in the period June-August 2013, through direct interview to transtibial amputees where a questionnaire was applied to measure Functional Amputee (FMA). Results: There was a predominance of males with 73.68%, being the main cause trauma presenting an incidence of 42.11%%. The levels of functional independence of the sample was observed that all patients have a very good degree of functionality using the same prosthesis that require some assistance at any time. Conclusion: Although the studies presented, it appears necessary further studies in this area mainly with assessment tools are specific to the population.
Keywords: Evaluation; transtibial amputation; functionality